relationship between problem focused coping and anxiety when dealing with the covid-19 pandemic for employees of grand mutiara hotel berastagi in 2021 - Lindawati Farida Tampubolon; Ice Septriani Saragih; Desta Lenta Indah Putri Zebua (Sean Institute, 2022)
Background: Anxiety is a feeling of fear that is not clear and is supported by a situation so that individuals will feel anxious as in the current COVID-19 pandemic situation. To overcome this, good coping is needed, one of which is problem focused coping which is an action directed at solving problems.Method: This study uses a cross sectional approach to 70 respondents and uses a quota sampling method. Collecting data using a questionnaire sheet given to each respondentResult: The problem focused coping of the employees of Grand Mutiara Hotel Berastagi is high as many as 51 people (72.9%) and low as much as . Anxiety when facing the COVID-19 pandemic among employees of Grand Mutiara Hotel Berastagi was 37 people (52.9%).Discussion: The results of the study obtained 72.9% high problem focused coping and 52.9% low anxiety. Based on the chi-square data analysis, the p-value = 0.001 (p<0.05) which means that there is a statistically significant relationship between problem focused coping and anxiety when dealing with the COVID-19 pandemic on employees of Grand Mutiara Hotel Berastagi in 2021